aYAP modRNA reduces cardiac inflammation and hypertrophy in a murine ischemia-reperfusion model - Chen, Jinmiao; Ma, Qing; King, Justin S; Sun, Yan; Xu, Bing; Zhang, Xiaoyu; Zohrabian, Sylvia; Guo, Haipeng; Cai, Wenqing; Li, Gavin; Bruno, Ivone; Cooke, John P; et al. (Life science alliance, 2020)
Myocardial recovery from ischemia-reperfusion (IR) is shaped by the interaction of many signaling pathways and tissue repair processes, including the innate immune response. We and others previously showed that sustained expression of the transcriptional co-activator yes-associated protein (YAP) improves survival and myocardial outcome after myocardial infarction. Here, we asked whether transient YAP expression would improve myocardial outcome after IR injury. After IR, we transiently activated YAP in the myocardium with modified mRNA encoding a constitutively active form of YAP (aYAP modRNA). Histological studies 2 d after IR showed that aYAP modRNA reduced cardiomyocyte (CM) necrosis and neutrophil infiltration. 4 wk after IR, aYAP modRNA-treated mice had better heart function as well as reduced scar size and hypertrophic remodeling. In cultured neonatal and adult CMs, YAP attenuated H2O2- or LPS-induced CM necrosis. TLR signaling pathway components important for innate immune responses were suppressed by YAP/TEAD1. In summary, our findings demonstrate that aYAP modRNA treatment reduces CM necrosis, cardiac inflammation, and hypertrophic remodeling after IR stress.
Keywords: Animals; RNA, Messenger; novorozená zvířata; reperfuzní poškození myokardu; transkripční faktory; Humans; Mice, Inbred C57BL; lidé; zvířata; messenger RNA; kardiomyocyty; Disease Models, Animal; Adaptor Proteins, Signal Transducing; Myocardial Reperfusion Injury; Injections, Intramuscular; myši inbrední C57BL; myokard; myši; editace RNA; Myocytes, Cardiac; Animals, Newborn; Myocardium; viabilita buněk; Neutrophil Infiltration; kardiomegalie; myokarditida; Apoptosis; Cells, Cultured; apoptóza; adaptorové proteiny signální transdukční; Myocarditis; Cardiomegaly; Mice; infiltrace neutrofily; Transcription Factors; Cell Survival; kultivované buňky; injekce intramuskulární; modely nemocí na zvířatech; RNA Editing